A barefoot doctor’s manual as a “medical bible” : medical politics and knowledge transmission in China - Fang, Xiaoping (2022)
This paper examines the origin, compilation and circulation of A Barefoot Doctor’s Manual Chijiao yisheng shouce 赤脚医生手册 ), exploring the relationship between medical politics and knowledge transmission in Chin a, and its impact on the promotion of Chinese medicine across the world. Barefoot doctors were a special group of rural medical practitioners active in a very special socio political context. Various editions of barefoot doctor manuals and textbooks were p ublished across China after the first publication of the Manual in 1969. The publication of these manuals and textbooks became an indelible hallmark of the Cultural Revolution (1966 1976), when political publications predominated. The Manual was not only a guide for barefoot doctors in their daily study and practice, but also a primary source of medical knowledge for ordinary people. In the middle of the 1970s, the Manual was translated into many languages and published worldwide. This paper argues that t he publication of A Barefoot Doctor’s Manual embodied a public oriented mode of knowledge t ransmission that emerged and was adopted during a very specific era, and though it was eventually substituted by a mode of training embedded in the formal medical ed ucation system, it demonstrated the impact of politics on medicine and health in the context of resource scarcity and low literacy. Changes in China’s geopolitical status, the West’s pursuit of alternative approaches to medicine and health, and the World H ealth Organization’s (WHO’s) concern over health universality and equity all contributed to the translation and circulation of the Manual , facilitating the dissemination of Chinese medicine worldwide. The paper thus presents empirical and theoretical contr ibutions to research on the relationship between medical politics and knowledge transmission in China.